Infection with different Neospora caninum strains causes differences in the glycosylation pattern in the uteri and placentae of Neospora caninum-infected heifers - Caspe, Sergio Gaston (2024)
Neospora caninum is an obligate intracellular parasite that causes abortion in ruminants. Different strains produce differences in the severity of disease outcomes. These differences may cause physiological or pathological changes in cells, modifying the intercellular interactions and intracellular transport pathways that could be evidenced by identifying the terminal sugars. This study aimed to characterize the oligosaccharide pattern in the bovine placenta and uterus after infection with tachyzoites of three different strains of N. caninum (Nc-1, Nc-6 Argentina and Nc Spain-7) during early gestation. Fourteen heifers were inoculated intravenously on day 70 of gestation with 2 × 108 N. caninum tachyzoites and samples of placentae and uteri were analysed by histology and lectin histochemistry. In the infected groups, severe placentitis was associated with changes in lectin binding in the vascular endothelium by Lens culinaris agglutinin (LCA), Pisum sativum agglutinin (PSA) and Ricinus communis I (RCA-I) lectins, in the epithelial cells of the endometrial glands by RCA-I, Dolichos biflorus agglutinin (DBA), succinylated wheat germ agglutinin, peanut agglutinin (PNA), concanavalin-A (CON-A), LCA, PSA and Phaseolus vulgaris erythroagglutinin (PHA-e), and in the trophoblast layer by PNA, CON-A, LCA, PSA, PHA-e, soybean agglutinin, RCA-I, DBA and Bandieraea simplicifolia agglutinin (BSA-I). The results suggest that N. caninum causes changes in the glycosylation pattern in the maternofetal interface tissues and might cause abortions in early gestation due to changes in the cellular structure of the placenta.